2006
DOI: 10.3354/ame044303
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of dissolved inorganic nitrogen, urea and amino acids in the Scheldt estuary: comparison of organic carbon and nitrogen uptake

Abstract: Uptake of dissolved ammonium, nitrate, nitrite, urea and amino acids was studied in the Scheldt estuary in different seasons over a salinity gradient. The importance of inorganic nitrogen sources was compared to that of urea and amino acids and the relative use of urea and amino acid nitrogen and carbon was studied. Urea and amino acids constituted up to 43 and 29% of total nitrogen uptake, respectively, and were of similar importance as inorganic substrates. Ammonium oxidation by nitrifiers and ammonium uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 66 publications
3
21
0
1
Order By: Relevance
“…The full incorporation of 15 N combined with incorporation of ~50% of the 13 C indicates that EAAO accounted for at least 50% of total microbial 15 N incorporation. These results are consistent with previous reports on the importance of EAAO in water column studies (Pantoja & Lee 1994, Mulholland et al 1998, 2002, Andersson et al 2006 and for the first time show the importance of EAAO in microbial nitrogen incorporation in sediment. Although extracellular oxidation of amino acids and subsequent resynthesis of amino acids inside the cells seems inefficient, it may actually be more economical than direct uptake of intact amino acids, which requires more energy than uptake of NH 4 + (Antia et al 1991 and references therein).…”
Section: N Versus 13 C: Amino Acidssupporting
confidence: 93%
See 3 more Smart Citations
“…The full incorporation of 15 N combined with incorporation of ~50% of the 13 C indicates that EAAO accounted for at least 50% of total microbial 15 N incorporation. These results are consistent with previous reports on the importance of EAAO in water column studies (Pantoja & Lee 1994, Mulholland et al 1998, 2002, Andersson et al 2006 and for the first time show the importance of EAAO in microbial nitrogen incorporation in sediment. Although extracellular oxidation of amino acids and subsequent resynthesis of amino acids inside the cells seems inefficient, it may actually be more economical than direct uptake of intact amino acids, which requires more energy than uptake of NH 4 + (Antia et al 1991 and references therein).…”
Section: N Versus 13 C: Amino Acidssupporting
confidence: 93%
“…5) confirms that part of the AA-13 C was transformed to 13 C-DIC. This uncoupled behavior of nitrogen and carbon from amino acids is consistent with results from previous studies on algal cultures (Algeus 1948, Stephens & North 1971, Palenik & Morel 1990, Antia et al 1991 and coastal waters (Schell 1974, Mulholland et al 2002, Andersson et al 2006, and conversion of amino acid carbon to DIC in a coastal sediment was reported by Christensen & Blackburn (1980).…”
Section: N Versus 13 C: Amino Acidssupporting
confidence: 92%
See 2 more Smart Citations
“…The large return of DIN in winter is most likely due to much smaller DON uptake coupled with excretion of DIN by macrofauna, while the lower summer returns may reflect assimilation and retention of N by microbes. The predominance of dark DON uptake throughout the study and the association of DON fluxes with Component 1 (Table 2) suggest that heterotrophic organisms were utilising DON compounds as either a carbon or nitrogen substrate (Andersson et al 2006). Uptake of DON was most pronounced in Cluster 3 (Table 3) and tended to increase during the second half of the night, which suggests that endogenous DON may become depleted within the benthos during the dark, leading microbes to remove dissolved substrates from the water column.…”
Section: Don Fluxesmentioning
confidence: 98%